A review of methods for assessment of cognitive function in high‐altitude hypoxic environments - Haojie Fan; Ying Meng; Lingling Zhu; Ming Fan; Du‐Ming Wang; Yong‐Qi Zhao (Brain and Behavior, 2024)
Abstract Hypoxic environments like those present at high altitudes may negatively affect brain function. Varying levels of hypoxia, whether acute or chronic, are previously shown to impair cognitive function in humans. Assessment and prevention of such cognitive impairment require detection of cognitive changes and impairment using specific cognitive function assessment tools. This paper summarizes the findings of previous research, outlines the methods for cognitive function assessment used at a high altitude, elaborates the need to develop standardized and systematic cognitive function assessment tools for high‐altitude hypoxia environments.